Budaya Gotong Royong Di Tengah Meningkatnya Individualisme Masyarakat Modern Di Kota Sorong - Natasya Virginia Leuwol; Merlyn R Leimena; Yun Maipauw; Stevani J. G Towara; Rachel A Kehek; Rivaldo G Patiro (CV. ITTC INDONESIA, 2026)
Mutual cooperation, known as gotong royong, is one of the fundamental cultural values of Indonesian society. However, the rapid development of technology and modernization has contributed to the growth of individualistic attitudes. This study aims to examine the impact of individualism on the culture of mutual cooperation and identify ways to preserve this cultural value in modern society. This research uses a qualitative method with a descriptive-analytical approach. Data were collected through literature review by analyzing books, scientific journals, and related articles.Thearticles Thefindings indicate that increasing individualism can reduce community participation in social activities. Therefore, cooperation among families, schools, and communities is necessary to maintain and strengthen the culture of mutual cooperation among younger generations.